Experience of a person becoming ill and family: oral life history - Rafaely de Cassia Nogueira Sanches; Mayckel da Silva Barreto; Roseney Bellato; Laura Filomena Santos Araújo; Sonia Silva Marcon; Cremilde Aparecida Trindade Radovanovic (Universidad de Alicante, 2019)
Objective: To understand the process of illness of an adult person with terminal chronic renal disease in dialysis and his family. Method: Oral Life History operationalized by the Interview in Depth with a young adult with chronic kidney disease. The questions, when made, sought to deepen the reflections and rescue their memories. The ensemble resulting from the complete transcription were transcribed into a literary first-person and subjected to analysis by sensible Reason. Results: Milky Way had been living the illness for six years, lived with his mother and his dog. The relationship of alterity, commitment, respect and concern were established between researchers and researched, allowing a deep understanding of the dimensions that make up the experience of becoming ill, especially the relationship with the family in the search for care. Conclusion: Has proved that he allowed them to know the experience in their own meanings and how family relate to the choices of care and healing.